Pantheon a new history of Roman religion - Rüpke, Jörg 1962- (Princeton University Press, 2018)
From one of the world's leading authorities on the subject, an innovative and comprehensive account of religion in the ancient Roman and Mediterranean worldIn this ambitious and authoritative book, Jörg Rüpke provides a comprehensive and strikingly original narrative history of ancient Roman and Mediterranean religion over more than a millennium—from the late Bronze Age through the Roman imperial period and up to late antiquity. While focused primarily on the city of Rome, Pantheon fully integrates the many religious traditions found in the Mediterranean world, including Judaism and Christianity. This generously illustrated book is also distinguished by its unique emphasis on lived religion, a perspective that stresses how individuals’ experiences and practices transform religion into something different from its official form. The result is a radically new picture of both Roman religion and a crucial period in Western religion—one that influenced Judaism, Christianity, Islam, and even the modern idea of religion itself.Drawing on a vast range of literary and archaeological evidence, Pantheon shows how Roman religion shaped and was shaped by its changing historical contexts from the ninth century BCE to the fourth century CE. Because religion was not a distinct sphere in the Roman world, the book treats religion as inseparable from political, social, economic, and cultural developments. The narrative emphasizes the diversity of Roman religion; offers a new view of central concepts such as "temple," "altar," and "votive"; reassesses the gendering of religious practices; and much more. Throughout, Pantheon draws on the insights of modern religious studies, but without "modernizing" ancient religion.With its unprecedented scope and innovative approach, Pantheon is an unparalleled account of ancient Roman and Mediterranean religion
Keywords: Religion -- History; Religions -- History; Antike; Religion; Geschichte; Römisches Reich; Mittelmeerraum